Inflammatory Response After Injection of Aqueous Gel Into Subarachnoid Space in Piglets. Issue 2 (1st March 2013) - Pintaric, Tatjana Stopar; Hadzic, Admir; Strbenc, Malan; Podpecan, Ozbalt; Podbregar, Matej; Cvetko, Erika
Abstract : Background: Ultrasound-guided neuraxial anesthesia requires the application of ultrasound gel between the transducer and the skin to avoid signal drop-off. As the needle is inserted, the gel may be introduced intrathecally. The purpose of this study was to examine the evidence of an inflammatory response in the subarachnoid space after intrathecal gel introduction. Methods: Twelve piglets were sedated with azaperone 0.5 mg/kg intramuscularly and anesthetized via face mask (2%–4% isoflurane in 50% air-oxygen mixture). After collection of cerebrospinal fluid by lumbar puncture with a 22-gauge needle (baseline), 0.2 mL of ultrasound gel mixed with 1 mL of saline was injected intrathecally into 9 piglets (gel group). In 3 piglets (control group), 1 mL of saline was administered. Behavioral and neurologic assessments were recorded on a 4-grade scale. Following the preinjection and postinjection cerebrospinal fluid collection, the piglets were killed, and samples of spinal cord with meninges were excised. Five cross sections (1 mm apart) were processed using immunohistochemistry. Results: After anesthesia, all piglets displayed short-lived mild (grade 1) motor and behavioral deficits. Mean ± SD protein concentrations in the gel and baseline samples were 14.1 ± 3.0 and 1.3 ± 0.5 g/L, respectively ( P = 0.001). No differences were found in protein concentration between baseline (1.8 ± 0.7 g/L) and control samples (2.8 ± 0.8 g/L) ( P = 0.4). In the gel group, numerous immunopositive cells were found in the pia, arachnoid, and inner layer of dura. Conclusion: Subarachnoid injection of ultrasound gel in piglets results in an inflammatory response within neuraxial space.